Ultraviolet shielding properties of cotton fabric supported by titanium-calcium hydroxyapatite solid solution particles. Issue 13 (July 2020) - Yasukawa, Akemi; Sohma, Ayano
Titanium-calcium hydroxyapatite (TiCaHap) particles were tried to be prepared by a wet method using starting solution with the ratio of Ti/(Ti + Ca) (denoted as [XTi ]) from 0 to 1 and pure TiCaHap particles were obtained from the condition with [XTi ] from 0 to 0.10. The particles were characterized by field emission scanning electron spectroscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy and spectrophotometry. Ultraviolet-visual (UV-vis) spectroscopy revealed that TiCaHap particles exhibit strong UV absorption under 380 nm. The UV absorption increased with an increase in concentrations of Ti 4+ . The TiCaHap prepared with [XTi ] = 0.05 was supported on cotton fabric. The UV shielding ability of the cotton fabric was enhanced by the addition of the TiCaHap particles. The influences of pre-treatment using a cationizing agent and washing with water or a sodium dodecyl sulfate solution for the cotton fabrics were also discussed.